POSTERIOR SCLERAL CONTRACTION TO TREAT MYOPIC FOVEOSCHISIS IN HIGHLY MYOPIC EYES. (May 2021) - Ye, Jie; Pan, An-Peng; Zhu, Shuangqian; Zheng, Linyan; Lu, Fan; Xue, An-Quan
Abstract : Purpose: To evaluate the efficacy of posterior scleral contraction to treat myopic foveoschisis (MF). Methods: The records of MF patients treated with posterior scleral contraction were reviewed. During posterior scleral contraction, a cross-linked fusiform strip from allogeneic sclera was used and designed axial length (AL) shortening amount was around 2.0∼3.0 mm based on preoperative AL. The middle part of the strip was placed at the posterior pole of the eye. After few aqueous humors were released, the strip was tightened to contract posterior sclera and shorten AL. Clinical data were collected at pre-operation (op) and post-op follow-ups for 12 months. Results: Twenty-four eyes were collected. The AL at pre-op, post-op 1-week, 3-month, 6-month, and 12-month were 29.84 ± 1.24, 27.39 ± 1.32, 27.73 ± 1.23, 27.86 ± 1.26, and 27.91 ± 1.29 mm. There was no AL difference between post-op 6-month and 12-month ( P = 0.242). The accumulated MF reattachment rate at post-op 1-week, 3-month, 6-month, and 12-month were 8.3%, 16.7%, 50.5%, and 95.8%. The best-corrected visual acuity at post-op 6-month and 12-month were 0.71 ± 0.39 (Snellen acuity 20/80) and 0.64 ± 0.37 (Snellen acuity 20/63), improving significantly compared with pre-op ( P = 0.006 and <0.001). Conclusion: The posterior scleral contraction was effective to treat MF. The AL stabilized after post-op 6-month and MF reattached gradually with improved visual acuity up to post-op 12-month. Abstract : The posterior scleral contraction was effective to treat myopic foveoschisis. Axial length was stabilized 6 months postoperation. The myopic foveoschisis would reattach gradually with continued improved visual acuity up to 12 months after surgery.